The affirmation of statehood in the administrative transformations linked to memory and human rights during the presidency of Néstor Kirchner (Clepsidra - Interdisciplinary Journal of Memory Studies, 2022)
This article analyzes the reconfiguration of the regime of government practices during the presidency of Néstor Kirchner through the affirmation of statehood from the administrative transformations point of view and linked to the issue of memory and human rights. In order to carry out this research, the article proposes a perspective that will draw on the works of Michel Foucault linked to governmentality. Through the analysis of a heterogeneous set of documents, the investigation focuses on the transformations that took place in the framework constituted by a multiplicity of state and non-state government authorities and the effects of such changes.
Keywords: Statehood; Memory; Human Rights; Governmentality.